Mathematical operation and symbol notation


  1. Statement
    L = M ≥ N;
    M > P;
    L < K.
    Conclusions
    I. K > P
    II. N < K
    1. If only Conclusions I is true
    2. if only Conclusions II is true
    3. if either Conclusions I or II is true
    4. if neither Conclusions I nor II is true
    5. if both Conclusions I and II are true

  1. View Hint View Answer Discuss in Forum

    Statement
    L = M ≥ N;
    M > P;
    L < K ;
    On combing both the statements, we get
    P < L = M ≥ N < k
    Conclusions
    I. K > P         (false)
    II. N < K       (true)

    Correct Option: B

    Statement
    L = M ≥ N;
    M > P;
    L < K ;
    On combing both the statements, we get
    P < L = M ≥ N < k
    Conclusions
    I. K > P         (false)
    II. N < K       (true)
    Hence, only Conclusions II is definitely true.


  1. Select the correct combination of mathematical signs to replace * signs and to balance the given equation.
    2 * 4 * 3 * 4 * 9
    1. + x = -
    2. x ÷ - =
    3. x - + =
    4. + - = +

  1. View Hint View Answer Discuss in Forum

    2 x 4 - 3 + 4
    8 - 3 + 4
    = 9

    Correct Option: C

    2 x 4 - 3 + 4
    8 - 3 + 4
    = 9



  1. If '+' means '-' '-' means 'x' , 'x' means '÷' and '÷' means '+' Which combination will give you the value of '0' in 42*4*12*20*9?
    1. ÷ + - x
    2. ÷ - + x
    3. - ÷ x +
    4. x - ÷ +

  1. View Hint View Answer Discuss in Forum

    The given expression is 42*4*12*9 = 0
    From option (c), 42, - 4 ÷ 12 x 20 + 9
    By coding, the equation becomes,
    LHS ⇒ 42 x 4 + 12 ÷ 20 - 9
    By applying the operations in sequence, from left to right,
    168 + 12 ÷ 20 - 9
    180 ÷ 20 - 9
    9 - 9 = 0 = R.H.S.

    Correct Option: C

    The given expression is 42*4*12*9 = 0
    From option (c), 42, - 4 ÷ 12 x 20 + 9
    By coding, the equation becomes,
    LHS ⇒ 42 x 4 + 12 ÷ 20 - 9
    By applying the operations in sequence, from left to right,
    168 + 12 ÷ 20 - 9
    180 ÷ 20 - 9
    9 - 9 = 0 = R.H.S.


  1. If - mean x , x means + , + means ÷ and ÷ means -. then
    40 x 12 + 3 - 6 ÷ 60 = ?
    1. 44
    2. 16
    3. 7.95
    4. 4

  1. View Hint View Answer Discuss in Forum

    40 + 12 ÷ 3 x 6 - 60
    = 40 + 4 x 6 - 60
    = 40 + 24 - 60
    = 64 - 60 = 4

    Correct Option: D

    40 + 12 ÷ 3 x 6 - 60
    = 40 + 4 x 6 - 60
    = 40 + 24 - 60
    = 64 - 60 = 4



  1. If + mean x, - means + , ÷ means + , x means - then the value of 162 x 52 - 26 ÷ 15 + 5
    1. 247
    2. 235
    3. 875
    4. 215

  1. View Hint View Answer Discuss in Forum

    162 - 52 ÷ 26 + 15 x 5
    = 162 - 2 + 75 = 235

    Correct Option: B

    162 - 52 ÷ 26 + 15 x 5
    = 162 - 2 + 75 = 235